Pengaruh Green Recruitment, Green Development dan Green Employee Relations Terhadap Employee Engagement pada Bank Syariah Nasional (BSN) Kantor Cabang Bengkulu - Heni Nurlara; Herlina Yustati; Miko Polindi (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This study aims to analyze the influence of Green Recruitment, Green Development, and Green Employee Relations on Employee Engagement at the National Sharia Bank (BSN) Bengkulu Branch Office, while raising the issue of the importance of integrating sustainability values ​​in strengthening employee engagement. The study uses associative research with a quantitative approach. The population in this study were all 39 employees, with a saturated sampling technique so that the entire population was used as a sample. Data were collected through distributing questionnaires using a Likert scale and analyzed using multiple linear regression with the help of SPSS. The results of the study indicate that each variable Green Recruitment, Green Development, and Green Employee Relations partially influences Employee Engagement. Simultaneously, the three variables have a positive and significant effect on Employee Engagement with a significance value of <0.05. The coefficient of determination (R²) value of 0.674 indicates that 67.4% of the variation in Employee Engagement can be explained by the three independent variables, while the rest is influenced by other variables outside the research model. These findings confirm that strengthening sustainability-based Green Human Resource Management practices plays a strategic role in increasing engagement, loyalty, and work enthusiasm of Islamic banking employees.